Prophylactic antineoplastic activity of Toxoplasma gondii RH derived antigen against ehrlich solid carcinoma with evidence of shared antigens by comparative immunoblotting - Maha M. Eissa; Maha R. Gaafar; Layla K. Younis; Cherine A. Ismail; Nahla El Skhawy (Infectious Agents and Cancer, 2023)
Abstract Background With cancer cases escalation, an urgent request to develop novel combating strategies arise. Pathogen-based cancer-immunotherapy is getting more consideration. Autoclaved parasitic antigens seem promising candidates, taking steadily their first steps. Our aim was to examine the prophylactic antineoplastic activity of autoclaved Toxoplasma vaccine (ATV) and to test for the shared antigen theory between Toxoplasma gondii and cancer cells. Methods Mice were immunized with ATV followed by Ehrlich solid carcinoma (ESC) inoculation. Tumor weight, volume, histopathology, and immunohistochemistry for CD8+ T cells, Treg cells and VEGF were assessed. In addition, the proposed shared antigen theory between parasites and cancer was also verified using SDS-PAGE and immunoblotting. Results Results revealed powerful prophylactic activity of ATV with 13.3% inhibition of ESC incidence, significant reduction in tumor weight and volume in ATV vaccinated mice. Immunologically, significantly higher CD8+T cells and lower FOXP3+ Treg cells surrounded and infiltrated ESC in ATV immunized mice with higher CD8+T/Treg cells ratio and significant antiangiogenic effect. Moreover, SDS-PAGE and immunoblotting showed four shared bands between Ehrlich carcinoma and ATV of approximate molecular weights 60, 26, 22 and 12.5 KDa. Conclusion Exclusively, we demonstrated a prophylactic antineoplastic activity of autoclaved Toxoplasma vaccine against ESC. Moreover, to the best of our knowledge this is the first report highlighting the existence of cross-reactive antigens between Toxoplasma gondi parasite and cancer cells of Ehrlich carcinoma.